2018
DOI: 10.1021/acsomega.8b00823
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Composites Developed from PBAT/PLA Binary Blends and Silk Powder: Compatibilization and Performance Evaluation

Abstract: Silk fibroin powder and biodegradable polybutylene adipate terephthalate (PBAT)/poly lactide (PLA) blends were melt-mixed together to fabricate natural and synthetic polymers as possible new sources of biomaterials. Morphological observations conducted through scanning electron microscopy indicated poor dispersion of the silk powder agglomerates, which resulted from strong hydrogen interactions between silk powder chains in the PBAT/PLA matrix. Although the silk powder agglomerates decreased the mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 38 publications
3
44
1
Order By: Relevance
“…EO was added only in the formulations that showed enhanced mechanical properties and it was fed separately with another lateral feeder. A fixed quantity of EO equal to 2 wt.% was chosen on the basis of literature works [ 17 , 54 , 56 , 57 , 58 , 59 ] but also considering the minimum quantity settable in the extruder that guaranteed a constant feeding without dosage problems. The blends containing EO are indicated in brackets and followed by the letter J in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…EO was added only in the formulations that showed enhanced mechanical properties and it was fed separately with another lateral feeder. A fixed quantity of EO equal to 2 wt.% was chosen on the basis of literature works [ 17 , 54 , 56 , 57 , 58 , 59 ] but also considering the minimum quantity settable in the extruder that guaranteed a constant feeding without dosage problems. The blends containing EO are indicated in brackets and followed by the letter J in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…However, PLA has limitations of brittleness and low heat resistance. Research has shown that blending with ductile polymers, i.e., poly(butylene adipate-co-terephthalate) (PBAT), poly(butylene succinate) (PBS), polycaprolactone (PCL) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and incorporating with particulate fillers and reinforcing fibers [ 25 , 26 , 27 , 28 , 29 ], can improve the limitations of PLA. From our previous study, the binary blend composites from PLA and PBAT blends (PLA/PBAT) and composites with nano talc (PLA/PBAT/nano talc) at 70/30/0/10 exhibited good toughness and printability, and can be presented as alternative filaments in FDM 3D printing [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Storage modulus and loss modulus of the blends and the composites were also higher than neat PLA as presented in Figure 4(b) and 4(c). It was considered that PBAT has long and flexible molecular chains resulting in elastic deformation due to molecular entanglement [5,22]. In addition, nano talc inhibited the movement of the polymer chains, which induced stiffness and solid like of molten polymer, especially at low frequency [14,27,[37][38][39].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…Nevertheless, PLA is known for its brittleness, low elongation at break, low impact strength, slow crystallization, and low heat distortion temperature. The incorporation of polymer blends and composites can overcome these drawbacks of PLA [17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation